Gender-Based Choice of Politeness Strategies in Interviews by Desi Anwar with Queen of Denmark Margrethe II and President Erdogan - Arianti, Theresia; Yutika Seli, Fenny (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Politeness strategies are a crucial element in conversations. Choosing the appropriate politeness strategies would lead to a smooth talk between the Speaker (S) and the Hearer (H). Preferred politeness strategies are different among different racial groups and also genders. In the case of an interview, the interviewer needs to suit his/her choice of politeness strategies to the interviewee’s preference so that the interviewee would feel comfortable in answering the interview questions. Thus, this current study aims to (1) examine the politeness strategies used by Desi Anwar in the interviews with Queen of Denmark Margrethe II and President Erdogan; (2) examine whether or not the choices of politeness strategies follow the preferred politeness strategies for men and women. The research questions are 1) What politeness strategies are used by Desi Anwar in the interviews with Queen of Denmark Margrethe II and President Erdogan? (2) Do the choices of politeness strategies follow the preferred strategies for men and women? The findings show that in interviewing Queen Margrethe II, Desi Anwar used to notice H, including both S and H, seeking agreement, being optimistic, and giving compliments as the politeness sub-strategies; one of them, i.e., compliment, is in line with females’ preferred politeness sub-strategies. However, in interviewing President Erdogan, Desi Anwar does not give any politeness sub-strategies preferred by males. It shows that it is easier for Desi Anwar to choose the appropriate politeness sub-strategies when she has an interviewee of the same gender.